2016
DOI: 10.1002/jor.23403
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of radial extracorporeal shock wave treatment for chronic plantar fasciopathy: A prospective, randomized, placebo-controlled trial with two years follow-up

Abstract: Numerous randomized controlled trials (RCTs) demonstrated efficacy and safety of extracorporeal shock wave therapy (ESWT) for chronic plantar fasciopathy (cPF). However, only two such RCTs investigated a follow-up period of more than 1 year, both applying focused ESWT. Corresponding data for radial ESWT (rESWT) have not yet been reported. We therefore tested the hypothesis that rESWT is effective and safe for the management of cPF with long-term follow-up of 2 years. To this end n = 50 patients with cPF were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 28 publications
0
23
0
5
Order By: Relevance
“…However, another metaanalysis suggested that pain improvement and success rate correlated with energy intensity level, with outcomes improved most by highintensity SWT, followed by ICS, and lastly lowintensity SWT [47,48]. A different study indicated that SWT provided better outcomes than placebo at 24-month follow-up [49].…”
Section: Plantar Fasciitismentioning
confidence: 99%
See 1 more Smart Citation
“…However, another metaanalysis suggested that pain improvement and success rate correlated with energy intensity level, with outcomes improved most by highintensity SWT, followed by ICS, and lastly lowintensity SWT [47,48]. A different study indicated that SWT provided better outcomes than placebo at 24-month follow-up [49].…”
Section: Plantar Fasciitismentioning
confidence: 99%
“…Comparison of these conflicting results indicates that there is still significant ambiguity regarding the extent and duration of effects of each therapy. ICS, PRP, and SWT have all been reported as safe with side effects limited to brief erythema or throbbing pain at the therapy site [38,39,46,47,49]. Studies have shown that PRP is associated with decreased requirement for reinjection or surgery in the long term and positive effects on soft tissue regeneration and inflammation reduction, but its higher cost must also be considered when choosing a treatment [38,45].…”
Section: Plantar Fasciitismentioning
confidence: 99%
“…Also, the feeling of the pulse is soft, as it has a gentle curve, enabling the patients to receive high energy treatment comfortably. Moreover, RSWT has a shock wave intensity that does not cause cavitation of cells, minimizing damage to tissues and cells in the human body [18].…”
Section: A Shock Wave Generation Methodsmentioning
confidence: 99%
“…Multiple research studies have proved that ESWT improves the microcirculation, inhibits the inflammatory response, promotes neural functional recovery, and stimulates osteoblast and the chondrocyte activity. rESWT has been used to treat chronic pain associated with diseases such as plantar fasciitis, carpal tunnel syndrome, chronic distal biceps tendinopathy, and lateral epicondylitis . Although rESWT is now an accepted therapeutic method to relive pain associated with nonimmune damage, its use in the treatment of RA has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…rESWT has been used to treat chronic pain associated with diseases such as plantar fasciitis, carpal tunnel syndrome, chronic distal biceps tendinopathy, and lateral epicondylitis. [4][5][6][7] Although rESWT is now an accepted therapeutic method to relive pain associated with nonimmune damage, its use in the treatment of RA has not been reported. In this study, we used rESWT in RA patients with arthralgia that was not adequately controlled with medication therapy, and examined its effects on pain relief and functional recovery.…”
Section: Introductionmentioning
confidence: 99%